Leptospirosis and melioidosis coinfection presenting as acute respiratory distress syndrome and osteomyelitis: Case report and systematic review - Manoj Kumar Panigrahi; Shakti Kumar Bal; Tara Prasad Tripathy; Akshaya Moorthy; Swadesh Kumar Mohanty; Ashoka Mahapatra; Sourin Bhuniya (Journal of Infection in Developing Countries)
Introduction: Leptospirosis and melioidosis are common in tropical and temperate climates and can be acquired by exposure to contaminated water and soil. However, concomitant leptospirosis and melioidosis infection is rarely described in the literature. We report a case of leptospirosis-melioidosis coinfection and systematically review the literature.